Analisis Strategi Polri Melalui Sosialisasi Bhabinkamtibmas dalam Upaya Peningkatan Minat Pendidikan Gen-Z - Lattu, Makudali Kamahati; Sorey, Oldrie; Rumambi, Githa (ITB AAS Indonesia Surakarta, 2024)
Bhabinkamtibmas have strong motivation to take part in education and training, so that they are more passionate and enthusiastic about learning. Evaluation of Community Policing Policy shows that there is novelty value from this research, making Bhabinkamtibmas a medium for the National Police in carrying out the basic tasks of the state, namely educating citizens from all perspectives. Qualitative research method with an exploratory approach. Research population of Rumbia village community. The sampling technique used in this research was total sampling, namely 80 families with 28 Gen Z children. The number of GEN Z in Rumbi village is 28 people, 1 person has succeeded in holding D3 and 2 people have S1. Currently, there are no children in Rumbia who criticize education at universities. There are 80 heads of families. The reasons behind the desire of Gen-Z and the Alpha generation to obtain higher education are: distance traveled and economic factors. It is hoped that this research can increase public awareness in Rumbia village, South Langowan District regarding the importance of increasing Generation Z's interest in learning in order to increase the existence of adequate education and be able to compete in the world of work in the future. There needs to be more collaboration between village officials and the government to find solutions so that infrastructure is available for generation Z to get adequate transportation access. Keywords: Bhabinkamtibmas; Education; Gen-Z; Police Strategy; Public